Open Transcatheter Multivalve Replacement in Degenerated Valve Prostheses in High-Risk Patients with Endocarditis - Zubarevich,Alina (2021)
Abstract Multivalve redo procedures carry a high surgical risk. We describe an alternative surgical treatment for patients presenting with severely degenerated aortic and mitral valve prostheses who have to undergo open surgery due to endocarditis. Open transcatheter multivalve implantation is a feasible bailout strategy in high-risk patients to save cross-clamp and procedural times to reduce morbidity and mortality.